1999
DOI: 10.3109/08820139909022724
|View full text |Cite
|
Sign up to set email alerts
|

Preferential enhancement of B cell IgA secretion by intestinal epithelial cell-derived cytokines and interleukin-2

Abstract: Intestinal epithelial cells (IEC) are known to secrete a number of important cytokines. Recently, we determined that IEC-derived IL-6 and TGF-beta could enhance IgA secretion and suppress IgM secretion by isolated mucosal B cells. However, since the IEC-derived cytokines must function in the context of locally produced T cell cytokines, the effect of IEC- and T cell-derived cytokines on mucosal B cell immunoglobulin secretion was determined. Using 4 day culture supernatants (IEC-SN) from the rat IEC-6 intestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…We assessed the fecal levels of IL6, IL8, IL12, TNF‐α, and IFN‐γ, which are typical Th‐1 pro‐inflammatory cytokines, and TGF‐β and IL10, regulatory cytokines capable of suppressing inflammatory responses 30 . In addition to its well‐known pro‐inflammatory role, IL6 also possesses anti‐inflammatory properties exerted through its ability to stimulate IgA secretion 31 , 32 . This evidence may explain why, in our study, the significant decrease in IL6 levels is also accompanied by a decrease in fecal IgA levels after treatment with LCDG, but not placebo 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the fecal levels of IL6, IL8, IL12, TNF‐α, and IFN‐γ, which are typical Th‐1 pro‐inflammatory cytokines, and TGF‐β and IL10, regulatory cytokines capable of suppressing inflammatory responses 30 . In addition to its well‐known pro‐inflammatory role, IL6 also possesses anti‐inflammatory properties exerted through its ability to stimulate IgA secretion 31 , 32 . This evidence may explain why, in our study, the significant decrease in IL6 levels is also accompanied by a decrease in fecal IgA levels after treatment with LCDG, but not placebo 31 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, higher production of IL-6 mRNA was observed in the postbiotic group indicating the activation of humoral immune response which assists B cells in mounting potent antibody responses 46 . This can also be related to higher production and secretion of IgA by the B-cells in the mucosa of jejunum 4749 . The cytokines involved in pro-inflammatory response such as IL-1β and IL-6 were reported to induce the production of cytokines that enhance the immune response 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal IgA secretion is mediated by epithelial cytokines, being elicited by transforming growth factor (TGF)-b and potentiated by IL-6 ( Fig. 5) (Goodrich & McGee, 1999). Taken together, these studies highlight the potential of both live and heat-killed L. gasseri to influence the host immune system.…”
Section: Immune System Regulationmentioning
confidence: 84%
“…These cytokines may contribute to the proliferation and differentiation of natural killer (NK) cells, which was observed in the analysis of splenic NK cells from mice fed L. gasseri TMC0356. 5) (Goodrich & McGee, 1999). Purified microbial RNA also suppressed CD4 + T cells, suggesting that nucleic acids of L. gasseri may play a role in immunomodulation (Yoshida et al, 2011).…”
Section: Immune System Regulationmentioning
confidence: 97%